Advances in molecular regulation and function of LDLR family in viral infection - Yao, Qing; Gong, Jun; Lu, Helin; Liu, Wu; Ding, Liqiong (Frontiers in Microbiology, 2025)
The low-density lipoprotein receptor (LDLR) family represents a crucial interface between cellular cholesterol homeostasis and viral pathogenesis. This review systematically examines the dual roles of these receptors in viral infections, encompassing both their well-established function as entry receptors for various viruses and their emerging role as regulators of viral replication through lipid metabolic pathways. The LDLR family mediates exogenous cholesterol uptake that supports viral proliferation while simultaneously suppressing endogenous cholesterol synthesis. This suppression triggers endoplasmic reticulum cholesterol depletion, which activates the STING-TBK1 signaling axis, thereby establishing a potent antiviral state. These opposing mechanisms reveal the complex involvement of the LDLR family in viral infections. This article aims to synthesize current understanding of these processes and explore the translational potential of targeting the LDLR-lipid-virus axis for developing novel antiviral strategies, while acknowledging the challenges in selectively modulating these dual functions for therapeutic purposes.